The Funding of Virtual Schools in Public Elementary and Secondary Education . - Luke J. Stedrak; Justin C. Ortagus; R. Craig Wood (Educational Considerations, 2012)
The advent of information technology throughout the United States has revolutionized the educational process and sparked the rapid growth of virtual education at the K-12 level in almost every state such that courses in every imaginable subject can now be offered outside the geographic constraints of school districts and traditional brick-and-mortar buildings.
Keywords: funding; Virtual Schools; elementary; secondary; education; Community schools